Blog Design For Dummies - Culbertson, Melissa (Hoboken, New Jersey John Wiley & Sons, Inc., 2013)
The average blogger does not typically have experience with design or coding, but that shouldn't deter them from having a professional-looking blog design. This friendly and easy-to-understand guide provides you with the tools you need to establish a creative, unique, and aesthetically memorable blog without having to learn how to code beyond some basic CSS. Whether you're looking to write for a major brand, become a brand ambassador, sell a product, acquire new clients, advocate for a cause, or simply tell a story, you'll find design tricks, helpful techniques, and invaluable advice for cr.
Includes Index and Illustrations.
Keywords: Blogs